A comparison of healthy children and children of patients with congenital hypothyroidism treated under treatment with Some evolutionary indicators - Seyedeh Raziyeh Khabiri; kokab namakin; Sajjad Rahimi Pordanjani (مجله دانشگاه علوم پزشکی بیرجند, 2017)
Background and Aim: Congenital hypothyroidism is one of the most important preventatives and curative causes of the growth and developmental disorder, which results in the implementation of a screening program for prevention of retardation. The purpose of this study was to compare the developmental indices of children with congenital hypothyroidism treated with healthy children in South Khorasan. Materials and Methods: In this case-control study, 30 children aged 18-24 months with hypothyroidism were diagnosed with screening Selected as a  case group. Also, 30 healthy children were matched with the case group, From health centers that children with hypothyroidism were covered by those centers, They were randomly selected as control group. These children were examined for evolutionary indicators. The data collection tool was a questionnaire for ages and stages of Ages & Stages Questionnaire(ASQ). Data were analyzed by SPSS software (version 15) and analyzed by means of Kolmogorov-Smirnov statistical tests and t-test. Independent samples were analyzed at the significant level of P=0.05. Results: It was found that mean somatic developmental indicators in congenital hypothyroid children, compared with those in the healthy group were significantly lower. However, the score for all children was above a standard deviation one unit. Conclusion: Although the mean developmental indices in hypothyroid children under treatment, based on Ages & Stages Questionnaires were lower than those in the control group, it was acceptable